Do Retail Investors Value Environmental Impact? A Lab-in-the-Field Experiment with Crowdfunders - Christoph Siemroth; Lars Hornuf (Center for Economic Studies and ifo Institute (CESifo), 2021)
Are investors willing to give up a higher return if the investment generates positive environmental impact? We investigate this question with a decision experiment among crowdfunders, where they choose between a higher return or environmental impact. Overall, 65% of investors choose environmental impact at the expense of a higher return for sufficiently large impact, 14% choose impact independent of the magnitude of impact, while 21% choose the higher return independent of impact. Combining the experimental data with historical investments, we find that investors allocate a larger share of funds to green projects if they value environmental impact more, and if they expect green projects to be more profitable. These findings suggest that investors have a preference for positive environmental impact, and satisfy it by investing in green projects. We further show that the preference for environmental impact is distinct from a preference for positive social impact. Finally, we introduce new survey measures of impact for future use, which are experimentally validated and predict field behavior.
Keywords: C93; D14; D90; G32; 330; debt crowdfunding; environmental impact; ESG; green investments; social impact; sustainable finance